The Correlation Between Self-Directed Learning on YouTube and English Speaking Achievement - Rumiyah Rumiyah (Journal of English for Academic and Specific Purposes (JEASP), 2026)
English speaking proficiency is a crucial component of communicative competence; however, many English as a Foreign Language (EFL) learners continue to face difficulties in developing effective speaking skills due to limited opportunities for authentic practice and exposure. Drawing on the theory of self-directed learning, digital platforms such as YouTube have been recognized as valuable resources that may support autonomous language learning beyond the classroom. Nevertheless, evidence regarding the relationship between self-directed learning through YouTube and speaking achievement remains limited, particularly in Indonesian vocational school contexts. This study investigated the correlation between students’ self-directed learning on YouTube and their English speaking achievement at SMKN 4 Palembang. Employing a quantitative correlational design, the study involved 33 tenth-grade students selected through purposive sampling. Data were collected through a questionnaire measuring self-directed learning activities on YouTube and a speaking test assessing fluency, pronunciation, grammar, vocabulary, and comprehension based on Brown’s (2004) speaking assessment framework. Pearson Product-Moment correlation analysis revealed a positive but very weak correlation between self-directed learning on YouTube and speaking achievement (r = 0.116). The relationship was not statistically significant (p 0.05), indicating that the use of YouTube as an autonomous learning resource did not substantially contribute to students’ speaking achievement. These findings suggest that autonomous access to YouTube alone is insufficient to improve speaking performance without structured learning strategies and reflective engagement. This study contributes empirical evidence from an Indonesian vocational school setting and highlights the importance of integrating guided pedagogical support with YouTube-based learning to enhance EFL learners’ speaking competence